The emergence of magnetic ordering at complex oxide interfaces tuned by defects - D.-S. Park (Nature Portfolio, 2020)
In the interfaces of non-magnetic complex oxides, it is unclear which defects are responsible for the magnetic interfaces. Here, the authors find the B-site cation stoichiometry is crucial for the creation and control of magnetism at the interface between non-magnetic ABO3-perovskite oxides.